1995
DOI: 10.1111/j.1524-4725.1995.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma Diagnosis and Treatment

Abstract: Treatment recommendations unfortunately are based more on anecdotal than scientific data because of the rarity of the tumor and its recognized high risk. Most authors recommend wide local excision of the primary lesion and regional lymph node resection if lymph nodes are palpable followed by x-irradiation of both the postsurgical bed and lymph node basin. The role of elective lymph node resection in the absence of clinically positive nodes remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 151 publications
6
117
1
9
Order By: Relevance
“…Meeuwissen et al 3 15 Eleven (21%) of 53 patients suffered locoregional failure, and the 3-year actuarial locoregional control was 75%. In a review of the literature, Haag et al 16 reported that local recurrence developed in 26% to 44% of patients, and during the course of the disease, 55% to 66% of patients developed regional node metastases. Given that 28% of patients had gross disease at either the primary site or the nodes, and 36% had recurrence before registering on the study, these figures compare favorably with those in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meeuwissen et al 3 15 Eleven (21%) of 53 patients suffered locoregional failure, and the 3-year actuarial locoregional control was 75%. In a review of the literature, Haag et al 16 reported that local recurrence developed in 26% to 44% of patients, and during the course of the disease, 55% to 66% of patients developed regional node metastases. Given that 28% of patients had gross disease at either the primary site or the nodes, and 36% had recurrence before registering on the study, these figures compare favorably with those in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Early reported series quote rates of distant metastatic disease to be 30%, 14,16,17 with some as high as 70%. 8 This does suggest that chemotherapy may have had a positive influence in reducing distant metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is a highly aggressive skin cancer exhibiting neuroendocrine differentiation (1,2). Although the neoplasm remains infrequent, its incidence is on the rise (3).…”
Section: Introductionmentioning
confidence: 99%
“…Merkel cell carcinoma (MCC) is thought to be issued from Merkel cells (1,2). It is a highly aggressive skin cancer exhibiting neuroendocrine differentiation (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…25 Changes observed on chromosome 1p suggest that 1 or more tumor suppressor genes play a role in the development of MCC, and certain individuals may be predisposed to develop this tumor. 14,20 Deletions involving 1p35-36 are similar to those described for malignant melanoma, pheochromocytoma, and neuroblastoma, tumors known to originate from neural crest cells. 26 Mutations in the tumor protein 73 (p73) gene (p53-like transcription factor) have been observed in MCCs.…”
Section: Etiologymentioning
confidence: 62%